2018
DOI: 10.3389/fneur.2018.00767
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Sleep Disturbances in Movement Disorders

Abstract: Sleep dysfunction is recognized as a distinct clinical manifestation in movement disorders, often reported early on in the disease course. Excessive daytime sleepiness, rapid eye movement sleep behavior disorder and restless leg syndrome, amidst several others, are common sleep disturbances that often result in significant morbidity. In this article, we review the spectrum of sleep abnormalities across atypical Parkinsonian disorders including multiple system atrophy (MSA), progressive supranuclear palsy (PSP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 209 publications
(223 reference statements)
0
27
0
Order By: Relevance
“…The existing neuroimaging studies on the EDS symptom in PD patients have found EDS-related alteration at brain structural, functional, and metabolic levels (for review, see Yousaf et al, 2018b). PD-EDS showed dopamine transporter (DAT) uptake reduction in the caudate, which correlated with clinical EDS symptom (Yousaf et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing neuroimaging studies on the EDS symptom in PD patients have found EDS-related alteration at brain structural, functional, and metabolic levels (for review, see Yousaf et al, 2018b). PD-EDS showed dopamine transporter (DAT) uptake reduction in the caudate, which correlated with clinical EDS symptom (Yousaf et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown associations with EDS symptoms in PD including non-tremor dominant phenotype, autonomic dysfunction, depression, anxiety, and disorders of rapid eye movement sleep behavior (Simuni et al, 2015;Amara et al, 2017;Wen et al, 2017), the neural mechanism of EDS in PD remains poorly understood. The lack of correlation between EDS and disease severity of PD [Hoehn & Yahr stage (H&Y)] has led to the notion that the EDS might be associated with PD-specific pathology (Yousaf et al, 2018b). However, in vivo neuroimaging quantification has been used to detect early pathophysiological changes in PD with EDS (PD-EDS), potentially serving as a biomarker for disease progression and treatment monitoring (Chondrogiorgi et al, 2016;Wen et al, 2017;Ashraf-Ganjouei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 C]FLB-457, extra-striatal dopamine D2 receptor, Parkinson's disease, positron emission tomography, REM sleep behavior disorder estimate of developing PD when diagnosed with RBD for 14 years is as high as 91% (Yousaf et al, 2018). This makes RBD one of the strongest clinical predictors of synucleinopathy onset-particularly PD given its higher prevalence (Yousaf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Often times, these behaviors may be associated with violent or aggressive dreams (Schenck et al., 1986). The prevalence of RBD in the general population is 0.5% (Ohayon et al., 1997); however, half of the PD population have comorbid RBD (PD‐RBD+) (Yousaf et al., 2018). The risk estimate of developing PD when diagnosed with RBD for 14 years is as high as 91% (Yousaf et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been proposed for the etiology of sleep disturbances in PD (25, 26). PD is a subtype of synucleinopathy characterized by alpha-synuclein deposit in neurons and its following induction of neuron degeneration.…”
Section: Discussionmentioning
confidence: 99%